Global Epidemiology of Human Infections With Variant Influenza Viruses, 1959–2021: A Descriptive Study . (1st March 2022) - Chen, Xinghui; Wang, Wei; Qin, Ying; Zou, Junyi; Yu, Hongjie
Abstract: Background: Although human case numbers of variant influenza viruses have increased worldwide, the epidemiology of human cases and human-to-human transmissibility of different variant viruses remain uncertain. Methods: We used descriptive statistics to summarize the epidemiologic characteristics of variant virus infections. The hospitalization rate, case-fatality, and hospitalization-fatality risks were used to assess disease severity. Transmissibility of variant viruses between humans was determined by the effective reproductive number ( R e ) and probability of infection following exposure to human cases. Results: We identified 707 naturally infected cases of variant viruses from 1959 to 2021, and their spatiotemporal/demographic characteristics changed across subtypes. The clinical severity of cases of variant viruses was generally mild; patients older than 18 years with underlying conditions were associated with hospitalization. Of 69 clusters of human infections with variant viruses (median cluster size: 2), the upper limit of R e was 0.09 (H1N1v, H1N2v, and H3N2v: 0.20 vs 0.18 vs 0.05), whereas it was not significantly different from the pooled estimates for avian influenza A(H7N9) and A(H5N1) viruses (0.10). Moreover, contacts of H5N1 cases (15.7%) had a significantly higher probability of infection than contacts of individuals with H7N9 (4.2%) and variant virus infections (4.2%–7.2%). Conclusions: The epidemiology of cases of variant viruses varied across time periods, geographical regions, and subtypes during 1959–2021. The transmissibility of different variant viruses between humans remains limited. However, given the continuous evolution of viruses and the rapidly evolving epidemiology of cases of variant viruses, improving the surveillance systems for human variant virus infections is needed worldwide. Abstract : The clinical severity and human-to-human transmissibility of cases of variant viruses remain limited. Given continuous evolution of viruses and rapidly evolving epidemiology of cases of different variant viruses, improving surveillance systems for human infections with variant viruses is needed worldwide.